A Case of Advanced Primary Thyroid Double-Hit B Cell Lymphoma in Which Complete Remission has been Maintained After High-Dose Chemotherapy and Autologous Peripheral Blood Stem Cell Transplantation Performed During the Second Remission, with a Review of the Literature - Sekiguchi, Yasunobu (Springer India, 2014)
A 50-year-old woman who presented with a mass in the thyroid gland was diagnosed as having diffuse large B-cell lymphoma (DLBCL) by biopsy in August 2011. The tumor had a complex chromosomal karyotype, including 8q24 (C-MYC) and 18q21(BCL-2), and fluorescence in situ hybridization confirmed split signals of C-MYC and BCL-2. BCL-2/IgH and C-MYC/IgH fusion signals were also observed. Three courses of rituximab, cyclophosphamide, doxorubicin, vincristine, prednisolone (R-CHOP) therapy were given, followed by thyroid gland irradiation. She was achieved complete remission (CR). In January 2012, a mass appeared in the right breast, which was diagnosed as relapse by biopsy. CR was achieved again after the 4th course of R-CHOP therapy, and one course of rituximab, etoposide, methylprednisolone, cytarabine, cisplatin (R-ESHAP) therapy was given. Thereafter, CR has been maintained after high-dose chemotherapy and autologous peripheral blood stem cell transplantation. There have been only 3 reported cases of primary thyroid C-MYC and BCL-2 double-hit lymphoma, including the present case; 2 of the cases were cases of DLBCL. R-CHOP therapy, irradiation and autologous peripheral blood stem cell transplantation are expected to be effective for such patients.